Teacher's Role In Managing Character Education In Educational Institutions State Madrasah Aliyah In Banyumas - Nurfuadi Nurfuadi (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
The purpose of this study is to discuss character education in improving the quality of implementation and educational outcomes that lead to the achievement of the formation of character and noble character of students as a whole, integrated and balanced. Research Methods with a qualitative descriptive approach, in the formulation of the problem to explore and photograph social phenomena that will be thoroughly and in-depth examined that occur in schools. Data collection techniques were obtained through interviews with PAI teachers, PKN teachers and vice principals in the field of curriculum. Observations at the madrasa observe the social environment that occurs. Documentation studies in the form of literacy and archives as well as official meeting notes. Conclusion. Madrasah Aliyah Islamic Religious Education Teachers have a very important role in managing character education. An intelligent teacher figure will be able to carry out the mandate in educating students. Teachers are competent, professional and responsible. Teacher competencies are inherent and have trustworthy and exemplary values so that they are able to act decisively and systematically. Student character education can increase knowledge independently examine and personalize character values and noble character so that they are manifested in daily behavior.